Justice and the racial dimensions of health inequalities: A view from COVID‐19. (4th March 2022) - Ganguli‐Mitra, Agomoni; Qureshi, Kaveri; Curry, Gwenetta D.; Meer, Nasar
Abstract: In this paper, we take up the call to further examine structural injustice in health, and racial inequalities in particular. We examine the many facets of racism: structural, interpersonal and institutional as they appeared in the COVID‐19 pandemic in the UK, and emphasize the relevance of their systemic character. We suggest that such inequalities were entirely foreseeable, for their causal mechanisms are deeply ingrained in our social structures. It is by recognizing the conventional, un‐extraordinary nature of racism within social systems that we can begin to address socially mediated health inequalities.